Temperature-responsive fluorescent nano material as well as preparation method and application thereof
By designing the temperature-responsive fluorescent nanomaterial TPE-CSO, combined with its AIE and LCST characteristics, a temperature-responsive continuous light capture system that simulates photosynthesis in nature was constructed, solving the problem of difficulty in simulating the temperature response of photosynthesis in the existing technology, and achieving efficient photocatalytic oxidation and cracking reaction.
Patent Information
- Application Number
- CN202411820654.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The prior art is difficult to effectively simulate the temperature response characteristics of natural photosynthesis, and temperature-sensitive photocatalytic systems with continuous energy transfer function are relatively scarce.
A temperature-responsive fluorescent nanomaterial TPE-CSO is designed, which consists of hydrophobic dual-core fluorescent groups TPE and CS with hydrophilic oligoethylene glycol (OEG) groups, with aggregation-induced emission (AIE) characteristics and low critical solution temperature (LCST) behavior, which can self-assemble and form fluorescent nanoparticles in water and build a temperature-responsive continuous light capture system.
The system exhibits adjustable fluorescence emission and thermal sensitivity characteristics, can continuously produce reactive oxygen species under light conditions, and achieve an ultra-high catalytic efficiency of 97% in the photocatalytic oxidation and cracking reaction, simulates the temperature response phenomenon of natural photosynthesis, and maintains a high catalytic efficiency under temperature cycling.
Smart Images

Figure CN119899133A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic luminescent materials and supramolecular photocatalysis, and more specifically, to a temperature-responsive fluorescent nanomaterial simulating photosynthesis of plants in nature, a preparation method thereof, and an application thereof in photocatalytic oxidation cracking. Background Art
[0002] In photosynthesis in nature, the continuous energy transfer process is the key mechanism for efficiently delivering solar energy to the reaction center, which ensures the stable conversion and utilization of light energy. As an innovative technology that mimics this process, artificial light harvesting systems have attracted widespread attention in recent years in terms of solar energy capture, transmission and utilization. Light harvesting systems are the primary link in photosynthesis, and their working principles have been deeply studied, which has further promoted the construction of artificial simulation systems. Supramolecular self-assembly provides an effective strategy for constructing efficient artificial light harvesting systems. This strategy not only provides an ideal way to improve light harvesting efficiency, but also shows great application potential. Artificial light harvesting systems based on supramolecular self-assembly have made significant progress at the nanoscale, showing extremely high donor / acceptor ratios, excellent energy transfer efficiency and enhanced antenna effects, showing their great advantages as efficient light harvesting systems.
[0003] Another important feature of photosynthesis is the significant effect of air temperature on its efficiency. Temperature changes not only affect natural photosynthesis, but also play an important role in the efficiency and selectivity of artificial photocatalytic reactions. Photocatalytic processes usually rely on the dynamic regulation of the molecular structure of reactants and environmental conditions, and temperature fluctuations often cause changes in catalytic performance. Molecules with temperature-responsive properties, such as oligoethylene glycol (OEG) groups, have attracted widespread attention due to their unique hydrophilicity and temperature responsiveness. By combining OEG groups with other functional groups to form amphiphilic molecules, these molecules can self-assemble into stable nanoaggregates in aqueous media and exhibit lower critical solution temperature (LCST) behavior.
[0004] Thermosensitive photocatalytic systems designed based on these characteristics can provide new ways to regulate photocatalytic reactions and simulate the effects of temperature changes on chemical reactions. Although the research on thermosensitive light-harvesting catalytic systems is still in its early stages, especially thermosensitive photocatalytic systems with continuous energy transfer functions are still rare, the technological breakthroughs in this field undoubtedly have important research value and broad application prospects. Summary of the invention
[0005] The present invention provides a bionic temperature-responsive fluorescent nanomaterial, and applies it to a photocatalytic oxidation cracking reaction. The compound TPE-CSO included in the nanomaterial has aggregation-induced emission (AIE) characteristics and amphiphilicity, and can self-assemble into fluorescent nanoparticles in an aqueous solution. Based on this, the constructed temperature-responsive continuous light harvesting system exhibits adjustable fluorescence emission and thermosensitive properties. In addition, the oligoethylene glycol chain gives TPE-CSO an adjustable low critical solution temperature behavior, combined with continuous fluorescence resonance energy transfer (FRET) and LCST characteristics, so that the system has temperature-sensitive properties. Under illumination conditions, the system can continuously generate reactive oxygen species (ROS) and is applied to photocatalytic oxidation cracking reactions, showing an ultra-high catalytic efficiency of 97%. As the temperature increases, the reaction yield gradually decreases, and the light harvesting system still maintains a high catalytic efficiency after cycling 20 times between 25°C and 60°C. The system well simulates the phenomenon that photosynthesis in nature is inhibited in hot weather and recovered in cool weather. This system not only provides a new means of regulating photocatalytic reactions, but also provides an important reference for simulating the environmental adaptability of natural photosynthesis, and has broad application prospects.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] The first aspect of the present invention provides a temperature-responsive fluorescent nanomaterial, which is a nanoparticle formed by a compound TPE-CSO in an aqueous phase; the compound TPE-CSO comprises a hydrophobic binuclear fluorescent group tetraphenylethylene (TPE) and cyanostyrene (CS) as a parent core, and a temperature-responsive oligoethylene glycol (OEG) connected by a benzyloxy group as a hydrophilic chain; the structural formula of the TPE-CSO is shown in Formula I:
[0008]
[0009] Furthermore, in the temperature-responsive fluorescent nanomaterial, the concentration of the compound TPE-CSO in deionized water is greater than 42 μM.
[0010] Furthermore, the turbidity temperature of the temperature-responsive fluorescent nanomaterial at a concentration of 200 μM is 35.3°C. When the temperature is lower than the turbidity temperature, the temperature-responsive fluorescent nanomaterial solution remains transparent; when the temperature is higher than the turbidity temperature, the temperature-responsive fluorescent nanomaterial solution becomes turbid; the turbidity temperature of the temperature-responsive fluorescent nanomaterial decreases with increasing concentration. When the concentration increases from 100 μM to 500 μM, the turbidity temperature decreases from 38.0°C to 33.6°C.
[0011] The second aspect of the present invention provides a method for preparing the temperature-responsive fluorescent nanomaterial as described above, the method comprising: subjecting compound a and compound b to nucleophilic substitution to obtain the compound TPE-CSO; the structural formula of the compound a is shown in Formula II:
[0012]
[0013] The structural formula of the compound b is shown in Formula III:
[0014]
[0015] Furthermore, the preparation method specifically includes the following steps: adding an acetonitrile solution containing K2CO3 and compound a to a reaction container under a N2 atmosphere; then, dripping an acetonitrile solution containing compound b into the reaction container to obtain a mixed system; reflux the mixed system for 36 hours, and after the reaction is completed, cooling the mixture obtained by the reaction to room temperature and concentrating under reduced pressure to obtain a crude product; purifying the crude product by silica gel column chromatography to obtain a yellow-green viscous oily product, which is the compound TPE-CSO.
[0016] Furthermore, in the preparation method, the amount of each component is used in the following proportions: in the acetonitrile solution containing K2CO3 and compound a, K2CO3 is 0.35 g, 2.6 mmol; compound a is 0.80 g, 1.7 mmol; acetonitrile is 18 mL; in the acetonitrile solution containing compound b, compound b is 1.23 g, 1.9 mmol; acetonitrile is 6 mL; the molar ratio of compound a, compound b, and K2CO3 is 1:(1.1-1.2):(1.4-1.6); preferably, the volume ratio of the eluent of the column chromatography is DCM:MeOH increased from 200:1 to 50:1.
[0017] Furthermore, the preparation method also includes synthesizing compound a and compound b separately; preferably, the synthesis method of compound a is: triphenylethylene bromide and 4-methoxyphenylboronic acid are subjected to Suzuki-Miyaura coupling reaction, and then demethylated with boron tribromide to obtain compound a; preferably, the synthesis method of compound b is: starting from triethylene glycol monomethyl ether, first converting the hydroxyl group into a sulfonyl group, and then reacting with methyl gallate, and obtaining compound b after reduction and bromination.
[0018] The third aspect of the present invention provides a temperature-responsive continuous light harvesting system, wherein the temperature-responsive continuous light harvesting system uses a hydrophobic dye rhodamine 6G (Rh6G) as a first-step energy acceptor (A1), sulforhodamine 101 (SR101) as a second-step energy acceptor (A2), and a temperature-responsive fluorescent nanomaterial as described in any one of claims 1 to 3 as a donor (D); wherein the molar ratio of the donor, the first-step energy acceptor, and the second-step energy acceptor is 1000:20:0 to 1000:20:20. The light harvesting system can generate reactive oxygen species (ROS). The light harvesting system ([TPE-CSO] = 50 μM) is added to 0.5 mM 9,10-anthracenediylbis(methylene)diglutaric acid (ABDA) and N,N,N',N'-tetramethylphenylenediamine (TMPD) solutions (4 mL), and under the irradiation of an ultraviolet lamp, the ultraviolet-visible absorption spectrum is tested over time to confirm that singlet oxygen and superoxide free radicals ( 1 O2 and O2 ·- ) and other reactive oxygen species.
[0019] A fourth aspect of the present invention provides application of the temperature-responsive continuous light harvesting system as described above in the field of photocatalytic oxidative cracking reactions.
[0020] Furthermore, the temperature-responsive continuous light harvesting system is subjected to a temperature-responsive photocatalytic oxidative cracking reaction, comprising the following steps: the temperature-responsive continuous light harvesting system and 1,1-diphenylethylene are sequentially added to water, and reacted at room temperature for 12 hours under the irradiation of ultraviolet light; the temperature-responsive continuous light harvesting system and 1,1-diphenylethylene are sequentially added to water, and reacted at 30°C, 40°C, 50°C and 60°C for 12 hours under the irradiation of ultraviolet light, and the yield gradually decreases as the temperature rises; the temperature-responsive continuous light harvesting system is added to water, and the reaction is carried out at 25°C and 60°C for 5, 10, 15 and 20 times, respectively, and then 1,1-diphenylethylene is added, and the reaction is carried out at room temperature for 12 hours under the irradiation of ultraviolet light, and the catalytic efficiency is still maintained.
[0021] Compared with the prior art, the present invention has at least the following beneficial effects:
[0022] 1. The synthesis method of the compound involved in the present invention is simple, the raw materials are cheap and easily available, the molecular preparation cost is low, and it has high economy and operability.
[0023] 2. The present invention successfully constructed a supramolecular bionic temperature-responsive continuous light harvesting system, which can not only fully simulate the continuous energy transfer process in photosynthesis in nature, but also effectively reflect the effect of temperature changes on catalytic efficiency. The developed system has good temperature response reversibility and can be applied to the photocatalytic oxidation cracking reaction process to accurately adjust the catalytic efficiency by controlling the temperature.
[0024] 3. The molecular design of the compound TPE-CSO is ingenious, combining the hydrophobic end with AIE effect and the hydrophilic end with LCST behavior, showing the characteristics of amphiphilic molecules killing two birds with one stone. This design can not only self-assemble in the water phase, but also respond sensitively to temperature changes, enhancing the functional diversity of the molecule.
[0025] 4. In the molecular design of the compound TPE-CSO, the AIE property is stably expressed through the TPE and CS binuclear fluorophores at the hydrophobic end, while the OEG group at the hydrophilic end gives the molecule LCST behavior. In the aqueous phase, TPE-CSO can self-assemble into regular nanospheres. When the temperature rises, the hydrogen bonds between the OEG group and the water molecules are destroyed, causing the hydrophobic end (TPE and CS units) to loosen, thereby reducing the AIE effect and fluorescence intensity. The design is inspired by the phenomenon of "temperature-induced disassembly, thereby inhibiting photosynthesis efficiency" in photosynthesis in nature, and is highly bionic.
[0026] 5. The assembly of the compound TPE-CSO can achieve two-step continuous energy transfer. After the two energy transfers are completed, when the donor / acceptor ratio reaches D / A1 / A2=1000:20:20, the energy transfer efficiency is still as high as 44.0%, showing excellent energy transfer performance and ensuring the efficient operation of the light harvesting system.
[0027] 6. The temperature-responsive continuous light harvesting system based on the compound TPE-CSO can act as a photosensitizer to precisely control the photocatalytic process through temperature regulation. The system also exhibits excellent temperature reversibility and can maintain high catalytic performance after more than 20 temperature cycles, providing innovative ideas for efficient photocatalytic reactions under temperature regulation and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the technical solution of the present invention;
[0029] Figure 2 is the H NMR spectrum of compound TPE-CSO;
[0030] Figure 3 is the carbon NMR spectrum of compound TPE-CSO;
[0031] Figure 4 This is the high-resolution mass spectrum of compound TPE-CSO;
[0032] Figure 5 is the critical aggregation concentration (CAC) of compound TPE-CSO;
[0033] Figure 6 This is the system temperature response diagram for the transmittance experimental measurement of the compound TPE-CSO;
[0034] Figure 7 This is the temperature response fluorescence emission diagram of the compound TPE-CSO;
[0035] Figure 8 It is the two-step continuous energy transfer diagram of compound TPE-CSO;
[0036] Fig. 9 This is the temperature response photocatalytic oxidative cracking reaction diagram of the compound TPE-CSO. DETAILED DESCRIPTION
[0037] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0038] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0039] The present invention provides a temperature-responsive fluorescent nanomaterial, which is formed based on the supramolecular self-assembly of TPE-CSO molecules in an aqueous phase. The structural formula of the compound TPE-CSO is as follows:
[0040]
[0041] The compound TPE-CSO is prepared by nucleophilic substitution of compound a and compound b, and the reaction equation is:
[0042]
[0043] Compound a is Compound b is
[0044] The preparation method of the temperature-responsive fluorescent nanomaterial comprises the following steps: adding K2CO3 (0.35 g, 2.6 mmol) and a solution of compound a (0.80 g, 1.7 mmol) in acetonitrile (18 mL) to a three-necked flask under N2 atmosphere, then slowly dripping a solution of compound b (1.23 g, 1.9 mmol) in acetonitrile (6 mL) into the flask, and refluxing the obtained mixed system for 36 hours. After the reaction is completed, the reaction mixture is cooled to room temperature and concentrated under reduced pressure, and the crude product is purified by silica gel column chromatography to obtain a yellow-green viscous oily compound TPE-CSO (1.00 g, 0.95 mmol, 56%). TPE-CSO is added to deionized water, and self-assembly is driven by hydrophilic and hydrophobic forces to form nanoparticles.
[0045] The present invention also provides a temperature-responsive continuous light harvesting system, which uses a hydrophobic dye Rh6G as an acceptor 1 (A1), SR101 as an acceptor 2 (A2), and TPE-CSO as a donor (D), and the molar ratio of the donor to the acceptor D / A1 is 1000:1-1000:20 and the ratio of D / A1 / A2 is 1000:20:0-1000:20:20. It can be seen that the system constructs a light harvesting system with reversible temperature response by loading the hydrophobic dye Rh6G and SR101 on the temperature-responsive fluorescent nanomaterial and using fluorescence resonance energy transfer. The system, as a catalyst for the photocatalytic oxidative cracking reaction, exhibits a catalytic efficiency of 97%.
[0046] The temperature-responsive continuous light harvesting system is subjected to a temperature-responsive photocatalytic oxidation cracking reaction, which has an excellent catalytic efficiency of 97%; comprising the following steps:
[0047] Step 1, the temperature-responsive continuous light harvesting system ([TPE-CSO] = 100 μM) and 1,1-diphenylethylene were sequentially added into water (20 mL), and reacted at room temperature for 12 h under ultraviolet light;
[0048] Step 2, the light-harvesting system and 1,1-diphenylethylene are sequentially added into water (20 mL), and reacted at 30° C., 40° C., 50° C. and 60° C. for 12 h under ultraviolet light, and the yield gradually decreases as the temperature rises;
[0049] Step 3: Add the light-harvesting system into water (20 mL) and cycle at 25°C and 60°C for 5, 10, 15 and 20 times respectively, then add 1,1-diphenylethylene, and react at room temperature for 12 hours under ultraviolet light, and still have excellent catalytic efficiency.
[0050] Figure 1It is a schematic diagram of the technical route of the present invention, showing the molecular structure, self-assembly process and LCST behavior of the compound TPE-CSO, as well as the construction of a reversible temperature-responsive secondary energy transfer light-harvesting system and the photocatalytic oxidation cracking reaction of 1,1-diphenylethylene. The compound TPE-CSO composed of hydrophobic TPE and CS groups and hydrophilic oligoethylene glycol chains has both AIE properties and LCST properties. As the temperature continues to rise, the aqueous solution of TPE-CSO gradually changes from clear to turbid, and when the temperature drops to the original solution, it returns to its original clear state. The secondary energy transfer light-harvesting system and photocatalytic oxidation reaction also have reversible temperature response. When the temperature rises, the fluorescence intensity of the light-harvesting system will gradually decrease, and for the photocatalytic reaction, it will affect the phenomenon that the catalytic efficiency gradually decreases with the increase in temperature, but when the temperature drops to the original temperature, it has an efficient catalytic effect.
[0051] Example
[0052] Example 1
[0053] (1) Synthesis of TPE-CSO: Under N2 atmosphere, K2CO3 (0.35 g, 2.6 mmol), compound a (0.80 g, 1.7 mmol) and acetonitrile (18 mL) solution were added to a three-necked flask, and then a solution of compound b (1.23 g, 1.9 mmol) in acetonitrile (6 mL) was slowly added dropwise to the flask. The resulting mixed system was refluxed for 36 h. After the reaction was completed, the reaction mixture was cooled to room temperature and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography to obtain a yellow-green viscous oily compound TPE-CSO (1.00 g, 0.95 mmol, 56%).
[0054] The H NMR spectrum of compound TPE-CSO is as follows Figure 2 As shown: 1 H NMR (300MHz, CDCl3) δ (ppm) = 7.63 (d, J = 6.0Hz, 2H, Ar-H), 7.56 (d, J = 6.0Hz, 2H, Ar-H), 7.30 (s ,1H,-CH=C-),7.13-7.09(m,11H,Ar-H),7.07-6.98(m,8H,Ar-H),6.66(s,2H,Ar-H),4.98(s, 2H,-CH2-),4.17-4.16(m,6H,-CH2-),3.85(s,4H,-CH2-),3.79(s,2H,-CH2-),3.73-3.72(m, 6H,-CH2-),3.67-3.63(m,12H,-CH2-),3.55-3.53(m,6H,-CH2-),3.38(d,J=3.0Hz,9H,-CH3).
[0055] The NMR carbon spectrum of compound TPE-CSO is as follows Figure 3 As shown: 13 C NMR (75MHz, CDCl3): δ (ppm) = 159.5, 153.0, 146.2, 143.5, 143.4, 143.3, 142.3, 140.2, 140.1, 138.4, 132.0, 131.5, 131.4, 128.6, 128. 0,127.9,127.8,127.6,127.4,127.0,126.8,118.4,115.4,110.2,107.3,72.4,72.0,70.9,70.8,70.7,70.7,70.3,69.8,69.0,59.1.
[0056] The high-resolution mass spectrum of compound TPE-CSO is as follows Figure 4 Shown: HRMS (ESI) m / z:calcd for C 63 H 73 NO 13 .[M+Na] + =1074.4974,found=1074.4964.
[0057] According to the above experimental characterization, the structure of the compound TPE-CSO is determined as follows:
[0058]
[0059] (2) The compound TPE-CSO self-assembles in deionized water driven by hydrophilic and hydrophobic forces. The transmittance experiment determines that the critical aggregation concentration of TPE-CSO is 42 μM, that is, above this concentration, TPE-CSO assembles into nanoparticles.
[0060] The first characteristic of the compound TPE-CSO is that it is an amphiphilic molecule, which contains an OEG group as a hydrophilic end and a TPE and CS dual fluorescent group as a hydrophobic end. Above the critical aggregation concentration (CAC, the value of which is 42μM as determined by the transmittance experiment), TPE-CSO forms spherical nanoassemblies driven by hydrophilic and hydrophobic forces. CAC determination see Figure 5 ,in Figure 5 (a) is the transmittance of TPE-CSO in aqueous solution at 2-256 μM, Figure 5 (b) The critical aggregation concentration of TPE-CSO is 42 μM.
[0061] (3) The compound TPE-CSO exhibits significant temperature responsiveness due to the presence of temperature-responsive OEG (oligoethylene glycol ether) units. A 200 μM TPE-CSO aqueous solution was prepared, and its cloud point temperature under this condition was measured to be 35.3°C through a transmittance experiment.
[0062] The second characteristic of the compound TPE-CSO is its good water solubility. At low temperatures, the O atoms in its groups form a hydrogen bond network with water, forming a uniform phase. As the temperature rises, the hydrogen bonds are destroyed, the molecules change from hydrophilic to hydrophobic, the two phases separate, and the solution becomes turbid. The temperature corresponding to when the solution transmittance drops to half of the original transmittance is called the "cloud point temperature", also known as LCST, which gives TPE-CSO temperature responsiveness. Figure 6 , Figure 6 This is the system temperature response diagram for the TPE-CSO transmittance experimental measurement, where Figure 6 (a) is the turbidity point measurement diagram, Figure 6 (b) is the temperature response cycle diagram.
[0063] In addition, the temperature response is reversible and can maintain stable performance after more than 20 heating / cooling cycles. The corresponding fluorescence emission is also reversible with temperature rise and fall.
[0064] The third characteristic of the compound TPE-CSO is that it exists in different aggregation forms in water during the heating / cooling transition and the form of energy radiation is different, thus having thermoresponsive fluorescence. When the solution is at room temperature, the TPE-CSO molecules self-assemble into ordered nanospheres in which the TPE and CS parts are tightly packed, which greatly restricts the intramolecular motion, and the energy is mainly dissipated in the form of radiation, resulting in strong emission with a maximum peak at 508nm. In contrast, when the temperature rises, the molecules transform from hydrophilic to hydrophobic, these tightly packed TPE units become loose, and the form of non-radiative dissipated energy further increases, resulting in weakened fluorescence. Ultimately, when the temperature rises to 60.0°C, the emission intensity decreases by 79% compared to the initial intensity. It is worth noting that this temperature-responsive fluorescence weakening process of TPE-CSO is reversible, and the fluorescence can be quickly restored after cooling to room temperature. See Figure 7 , Figure 7 is the temperature response fluorescence emission diagram of TPE-CSO, where Figure 7 (e) is the histogram of fluorescence variation with temperature. Figure 7 (f) is the temperature response cycle diagram.
[0065] Example 2
[0066] In this embodiment, the supramolecular polymer formed by the compound TPE-CSO is used as the energy donor D, the hydrophobic fluorescent dye Rh6G is used as the receptor A1, and SR101 is used as the receptor A2. The preparation method is as follows:
[0067] First, the preparation of light-harvesting nanoparticles:
[0068] A 100 μM aqueous solution of TPE-CSO was prepared, and a donor-acceptor aqueous solution with a ratio of D / A1 / A2=1000 / 20 / 20 was prepared by loading Rh6G and SR101, and ultrasonicated for 3 min with shaking during the process, and the fluorescence intensity of the sample was measured by a fluorescence spectrophotometer;
[0069] The following solution ratios (D / A1 / A2) were prepared in the same way as above: 1000 / 20 / 6, 1000 / 20 / 8, 1000 / 20 / 10, 1000 / 20 / 12, 1000 / 20 / 14, 1000 / 20 / 16, 1000 / 20 / 20. Their fluorescence spectra were combined as shown in the following figure. Figure 8 shown.
[0070] The fourth characteristic of the compound TPE-CSO is that the hydrophobic binuclear TPE and CS it contains are groups with aggregation-induced emission. Therefore, TPE-CSO forms nanoparticles and aggregation-induced fluorescence enhancement occurs. This provides a prerequisite for the construction of an artificial light-harvesting system. By loading the hydrophobic dye Rh6G as the acceptor A1, SR101 as the acceptor A2, and the TPE-CSO group as the energy donor D, when the dye molecules are encapsulated in the limited space of the nanoparticles, the distance between the donor and the acceptor is close enough, creating sufficient conditions for FRET to occur. By studying the light-harvesting performance of the system, it was found that there was a good overlap between the absorption spectrum of Rh6G and the emission spectrum of TPE-CSO, and there was also a good overlap between the absorption spectrum of SR101 and the emission spectrum of TPE-CSO / Rh6G. Under the donor-acceptor ratio (D / A1 / A2=1000:40:40), the primary energy transfer efficiency (Φ ET ) is as high as 78.3%, and the secondary energy transfer efficiency (Φ ET ) can reach up to 44.0%. Figure 8 , Figure 8 is the two-step continuous energy transfer diagram of TPE-CSO, where Figure 8 (a) is the absorption and emission overlap diagram of TPE-CSO and Rh6G. Figure 8 (b) is the primary energy transfer spectrum. Figure 8 (c) is the absorption and emission overlap diagram of TPE-CSO / Rh6G and SR101. Figure 8(d) is the secondary energy transfer spectrum. In this embodiment, the ultrasonic instrument used is an ultrasonic cleaning machine commonly used in laboratories, and the frequency is 40kHz.
[0071] Second, energy transfer efficiency calculation:
[0072] The fluorescence spectra of TPE-CSO and TPE-CSO / Rh6G / SR101 were measured under 378 nm excitation;
[0073] Energy transfer efficiency (Φ ET ) is calculated by equation S1:
[0074] Φ ET =1-I DA / I D
[0075] Among them I DA and I D are the fluorescence intensities of TPE-CSO / Rh6G / SR101 and TPE-CSO / Rh6G at 562 nm when excited at 378 nm, respectively, where [TPE-CSO] = 1.0 × 10 -4 mol / L, [Rh6G] = 2.0 × 10 -6 mol / L. [SR101] = 2.0 × 10 -6 mol / L. Substituting the data into formula S1, we get D / A1 / A2=1000 / 20 / 20, and the energy transfer efficiency of energy transfer reaches 44.0%.
[0076] The energy transfer efficiencies of other ratios are calculated according to the above formula.
[0077] Example 3
[0078] Temperature-responsive photocatalytic reaction of compound TPE-CSO.
[0079] Step 1: Use a pipette to take TPE-CSO aqueous solution (D, 100 μL, 20 mM), Rh6G DMSO solution (A1, 20 μL, 2.0 mM) and SR101 DMSO solution (A2, 8 μL, 5.0 mM) into a 50 mL eggplant-shaped bottle, and then add deionized water (20 mL). After ultrasonic treatment for 5 minutes, 1,1-diphenylethylene (180 μL) was added, and the reaction was carried out at room temperature for 12 hours under ultraviolet light to finally generate an oxidative cleavage product, benzophenone, with a catalytic efficiency of up to 97%.
[0080] Step 2: The prepared photosensitizer (TPE-CSO / Rh6G / SR101) aqueous solution was placed in different temperature environments (25°C, 30°C, 40°C, 50°C and 60°C) for reaction for 12 hours. The experimental results showed that the catalytic efficiency gradually decreased with increasing temperature.
[0081] Step 3, the prepared photosensitizer (TPE-CSO / Rh6G / SR101) aqueous solution was repeatedly heated and cooled between 25°C and 60°C (5, 10, 15 and 20 times), and the catalytic efficiency was still maintained at an ultra-high level (≥90%).
[0082] It should be noted that the fifth characteristic of the compound TPE-CSO is that after continuous light capture (TPE-CSO / Rh6G / SR101), it can be used as a photosensitizer and can efficiently generate reactive oxygen species, including singlet oxygen and superoxide radicals ( 1 O2 and O2 ·- ), and showed excellent catalytic performance for the photocatalytic oxidative cracking of 1,1-diphenylethylene. The catalytic efficiency is significantly affected by temperature: at 25°C, the reaction yield is as high as 97%, but as the temperature increases, the catalytic efficiency gradually decreases, and the yield is only 27% at 60°C. In addition, the catalytic reaction has excellent temperature reversibility. After repeated heating and cooling cycles between 25°C and 60°C for 5, 10, 15 and 20 times, the continuous LHS aqueous solution still maintains an ultra-high catalytic efficiency (≥90%). See Fig. 9 , Fig. 9 The temperature-responsive photocatalytic oxidative decomposition reaction of TPE-CSO is shown in Figure 2. Fig. 9 (a) ABDA was used as a capture agent to detect the 1 O2 production, Fig. 9 (b) TMPD is used as a capture agent to detect O2 under different conditions ·- The production of Fig. 9 (c) is a bar graph of the efficiency of the photocatalytic reaction at different reaction temperatures (25°C, 30°C, 40°C, 50°C, 60°C). Fig. 9 (d) is a bar graph of the catalytic reaction efficiency of the continuous light harvesting system after heating / cooling cycles (5, 10, 15, and 20 times) at 25°C and 60°C.
[0083] The above are only preferred embodiments of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A temperature-responsive fluorescent nanomaterial, characterized in that: The temperature-responsive fluorescent nanomaterial is nanoparticles formed by the compound TPE-CSO in an aqueous phase; The compound TPE-CSO comprises hydrophobic binuclear fluorescent groups tetraphenylethylene and cyanostyrene as the parent core, and a temperature-responsive oligoethylene glycol connected by a benzyloxy group as the hydrophilic chain; The structural formula of the TPE-CSO is shown in Formula I:
2. The temperature-responsive fluorescent nanomaterial according to claim 1, characterized in that: In the temperature-responsive fluorescent nanomaterial, the concentration of the compound TPE-CSO in deionized water is greater than 42 μM.
3. The temperature-responsive fluorescent nanomaterial according to claim 2, characterized in that: The temperature-responsive fluorescent nanomaterial has a turbidity point temperature of 35.3°C at a concentration of 200 μM. When the temperature is lower than the turbidity point temperature, the temperature-responsive fluorescent nanomaterial solution remains transparent; and when the temperature is higher than the turbidity point temperature, the temperature-responsive fluorescent nanomaterial solution becomes turbid. The turbidity point temperature of the temperature-responsive fluorescent nanomaterial decreases with increasing concentration. When the concentration increases from 100 μM to 500 μM, the turbidity point temperature decreases from 38.0°C to 33.6°C.
4. The method for preparing a temperature-responsive fluorescent nanomaterial according to any one of claims 1 to 3, characterized in that: The preparation method comprises: subjecting compound a and compound b to nucleophilic substitution to obtain the compound TPE-CSO; The structural formula of the compound a is shown in Formula II: The structural formula of the compound b is shown in Formula III:
5. The method for preparing the temperature-responsive fluorescent nanomaterial according to claim 4, characterized in that: The preparation method specifically comprises the following steps: Under N2 atmosphere, an acetonitrile solution containing K2CO3 and compound a is added to a reaction container; subsequently, an acetonitrile solution containing compound b is added dropwise to the reaction container to obtain a mixed system; the mixed system is refluxed to react for 36 hours. After the reaction is completed, the mixture obtained by the reaction is cooled to room temperature and concentrated under reduced pressure to obtain a crude product; the crude product is purified by silica gel column chromatography to obtain a yellow-green viscous oily product, which is the compound TPE-CSO.
6. The method for preparing the temperature-responsive fluorescent nanomaterial according to claim 5, characterized in that: In the preparation method, the dosage of each component is carried out according to the following ratio: In the acetonitrile solution containing K2CO3 and compound a, K2CO3 is 0.35 g, 2.6 mmol; Compound a is 0.80 g, 1.7 mmol; acetonitrile is 18 mL; In the acetonitrile solution containing compound b, compound b is 1.23 g, 1.9 mmol; acetonitrile is 6 mL; The molar ratio of compound a, compound b and K2CO3 is 1:(1.1-1.2):(1.4-1.6); Preferably, the volume ratio of the eluent in the column chromatography is DCM:MeOH increased from 200:1 to 50:
1.
7. The method for preparing the temperature-responsive fluorescent nanomaterial according to claim 5, characterized in that: The preparation method further comprises synthesizing compound a and compound b separately; Preferably, the synthesis method of the compound a is: triphenylethylene bromide and 4-methoxyphenylboronic acid are subjected to Suzuki-Miyaura coupling reaction, followed by demethylation with boron tribromide to obtain the compound a; Preferably, the synthesis method of the compound b is: starting from triethylene glycol monomethyl ether, first converting the hydroxyl group into a sulfonyl group, then reacting with methyl gallate, and then reducing and brominating to obtain the compound b.
8. A temperature-responsive continuous light harvesting system, characterized in that: The temperature-responsive continuous light harvesting system uses the loaded hydrophobic dye rhodamine 6G as the first-step energy acceptor, sulforhodamine 101 as the second-step energy acceptor, and uses the temperature-responsive fluorescent nanomaterial described in any one of claims 1 to 3 as a donor; wherein the molar ratio of the donor, the first-step energy acceptor and the second-step energy acceptor is 1000:20:0 to 1000:20:
20.
9. Application of the temperature-responsive continuous light harvesting system as claimed in claim 8 in the field of photocatalytic oxidation cracking reactions.
10. The use according to claim 9, characterized in that The temperature-responsive continuous light harvesting system is subjected to a temperature-responsive photocatalytic oxidative cracking reaction, comprising the following steps: The temperature-responsive continuous light harvesting system and 1,1-diphenylethylene are sequentially added into water, and reacted at room temperature for 12 hours under the irradiation of ultraviolet light; The temperature-responsive continuous light harvesting system and 1,1-diphenylethylene are sequentially added into water, and reacted at 30° C., 40° C., 50° C. and 60° C. for 12 hours respectively under the irradiation of ultraviolet light, and the yield gradually decreases as the temperature rises; The temperature-responsive continuous light harvesting system was added to water and cycled at 25° C. and 60° C. for 5, 10, 15 and 20 times respectively, and then 1,1-diphenylethylene was added. The system was reacted at room temperature for 12 hours under the irradiation of ultraviolet light and still had catalytic efficiency.
Citation Information
Patent Citations
Supramolecular fluorescent material with multiple responses and preparation method thereof
CN116693421A
Temperature stimuli responsive supramolecular cascade light capture system and preparation method and application thereof
CN118290240A
Continuous light capture system based on neutral amphiphilic molecules as well as preparation method and application of continuous light capture system
CN118562489A
Continuous light capture system based on AIE type donor and preparation method and application thereof
CN118725852A